Structural phase transitions and magnetic and spectroscopic properties of the double perovskites Sr2Co1−xMgxTeO6 (x = 0.1, 0.2 and 0.5). Issue 30 (14th August 2015) - Orayech, B.; Ortega-San-Martín, L.; Urcelay-Olabarria, I.; Lezama, L.; Rojo, T.; Arriortua, María I.; Igartua, J. M.
<x xml:space="preserve">Abstract</x> Structural and magnetic properties of a series of double perovskites are investigated by X-ray and Neutron diffraction, EPR and magnetic susceptibility. The structural and phase-transitions analysis are done using symmetry mode-analysis approach.